Kewenangan dan Tanggung Jawab PPAT dalam Proses Pembebasahan Tanah untuk Kepentingan Umum - Putri, Deviana; Silviana, Ana (Universitas Muhammadiyah Ponorogo, 2025)
The land acquisition process requires the involvement of various parties, one of which is the Land Deed Making Officer (PPAT). PPAT has an important role in ensuring the validity of land administration through the creation of authentic deeds, such as deeds of sale and purchase, deeds of gift, and deeds of release of rights. In the context of land acquisition for public interest, the authority and responsibility of PPAT are very crucial in ensuring legal certainty for all parties involved. This study aims to find out and understand the authority of PPAT in the process of land acquisition for public interest and to analyze the legal responsibility of PPAT in making words related to land acquisition. The type of research used in this thesis is normative legal research, namely research that focuses on the study of laws and regulations, legal doctrine, legal principles, and relevant literature. This study is used to analyze the authority and responsibility of PPAT as regulated in the positive legal system in Indonesia, especially in the context of land acquisition for public interest. The results show that the PPAT's authority in land acquisition for public interest is to make authentic deeds related to the transfer of land rights, such as deeds of sale and purchase, deeds of release of rights, and deeds of gift. This authority is administrative in nature and does not include the assessment of compensation or determination of land acquisition policies and the legal responsibilities of the PPAT include ensuring the validity of documents and the identities of the parties, as well as ensuring that the transferred land is not in dispute. PPAT's negligence can have legal consequences, both administrative, civil, and criminal.